PENELITIAN TEKNOLOGI PROSES PENGOLAHAN MINUMAN REBUNG TABAH (Gigantocholoa nigrociliata) (The Research about Processing Technology of Tabah Bamboo Shoots (Gigantocholoa nigrociliata) Drink) - Syamsixman, Syamsixman (Baristand Industri Banda Aceh, 2013)
The research about processing technology of Tabah bamboo shoots drinkhad been done. It was aimed to find the right technique to produce a high quality andhealthy bamboo shoots drink. The research has two steps. The first step was aimed to findout the best blanching technique and CMC concentration that will be used in the secondstep. Several factors of blanching technique and CMC concentration were tested. Thefactors of blanching technique include the boiling media (water and 3% saline), blanchingtemperature (room temperature, 80 oC, and 100 oC) and blanching duration (0, 1, and 2 hours) which resulted in 13 different treatments, while concentration of CMC was variedin 5 different treatments (0.00; 0.01; 0.02; 0.03; 0.04 %). In the first steps all samples wasobserved both visually, for their stability and bitter taste of fresh bamboo shoots, andchemically, for its water, carbohydrat, dietary fiber, cyanide acid, sugar, and potassiumcontain of bamboo shoots drink. While in the next step, they were observed for theirdietary fiber, pH, plate count agar, sugar, potassium, cyanide acid, taste, and aroma. Thefirst research found out that the most important factor is blanching duration with 3%saline as boiling media for 15, 30, 45, and 60 minutes blanching duration and 0.02percent CMC concentrations. Those criteria was then applied in the second research. Itwas found out that using 3% saline as boiling media with 90 - 100 oC blanchingtemperature and 60 minutes blanching duration had been given the best result. Theproduct was its healthy because of its low cyanide acid contents (43.88 mg/kg) lesser thanFAO standard (50 mg/kg) and it also had good quality because of its good stability with3.5 hedonic scale (very like), high potassium amount (438.20 ppm), 0.85 percent dietaryfiber (w/w), 15% sugar, low pH (3.3), and low PCA (75 colony/g) lesser than nationalstandard SNI 01-3719-1995 (200 colony/g). It also had good taste with 3.2 hedonic scale(very like) and aroma with 3.3 hedonic scale (very like).